Peranan Komisi Informasi Dalam Mengawal Keterbukaan Informasi Publik Di Masa Kedaruratan Kesehatan (Pandemi) Covid-19 - Kadek Cahya Susila Wibawa (Administrative Law and Governance Journal, 2020)
Abstract The determination of the Covid-19 pandemic by WHO has had a tremendous impact on human life around the world, including in Indonesia. The Indonesian government responded to this health emergency by issuing various policy packages to prevent the spread and control of the spread of covid-19, including non-medical policies. The government is given the responsibility to convey information related to the Covid-19 pandemic accurately, effectively, and efficiently to the public as a manifestation of the principle of transparency as mandated by the 1945 Constitution of the Republic of Indonesia and the KIP Law. Examining the KIP Law, there were no exceptions regarding pandemic information as confidential information because the KIP Law regulates the obligation to immediately convey to the entire public regarding the potential for transmission of disease, especially a pandemic, such as the coronavirus pandemic. Information about a coronavirus pandemic can be categorized as information that threatens life. The Information Commission has a very significant (important) role in safeguarding information disclosure, especially information related to the spread and response to Covid-19 during this pandemic. The Information Commission carries out oversight (supervision) of the implementation of information disclosure as a form of the commitment of the Information Commission with the government in implementing the principles of good governance and democratization of government. Keywords: Good governance; Public information openness; Information Commission; Covid-19 pandemic. Abstrak Penetapan pandemi covid-19 oleh WHO telah memberikan dampak yang luar biasa bagi kehidupan manusia di seluruh dunia, termasuk di Indonesia. Pemerintah Indonesia menyikapi keadaan darurat kesehatan tersebut dengan mengeluarkan berbagai paket kebijakan untuk mencegah penyebaran dan penanggulangan penyebaran covid-19, termasuk kebijakan yang non medis. Pemerintah diberikan tanggung jawab untuk menyampaikan informasi terkait pandemi covid-19 secara akurat, efektif, dan efisien kepada masyarakat sebagai perwujudan prinsip transparansi sebagaimana amanat UUD NRI 1945 dan UU KIP. Menelisik UU KIP, tidak ditemukan pengecualian tentang informasi pandemi sebagai sebuah informasi yang bersifat rahasia, karena UU KIP tersebut mengatur tentang kewajiban untuk segera menyampaikan kepada seluruh masyarakat terkait adanya potensi ketertularan suatu penyakit terutama pandemi, seperti pandemi virus corona ini. Informasi mengenai pandemi virus corona ini dapat dikategorikan sebagai informasi yang mengancam hajat hidup. Komisi Informasi mempunyai peranan yang sangat siginifikan (penting) dalam mengawal keterbukaan informasi, khususnya informasi yang berkaitan dengan penyebaran dan penanggulan covid-19 di masa pandemi ini. Komisi Informasi melakukan pengawalan (pengawasan) terhadap pelaksanaan keterbukaan informasi sebagai wujud komitmen Komisi Informasi bersama pemerintah dalam melaksanakaan prinsip-prinsip good governance dan demokratisasi pemerintahan. Kata kunci:    Good governance; Keterbukaan informasi; Komisi Informasi; Pandemi Covid-19.